Green Finance as a Mediator of FDIs’ Impact on Energy Productivity and Environmental Sustainability in Resource-Intensive Sectors of GCC Countries - Hani, Umme (International Journal of Energy Economics and Policy, 2026)
This study aims to examine the role of green finance in linking resource-intensive sectors in GCC countries to improved energy productivity and environmental sustainability through the use of foreign direct investment (FDI). The study applies ARDL models to data collected from 1990 to 2023 in order to comprehend the long-term and short-term relationships among FDI, green finance, research and development, trade openness, GDP, and renewable energy usage. The findings highlight the significance of foreign direct investment (FDI), research and development (R&D), and green financing in bolstering industrial strength and energy productivity, as well as in achieving environmental objectives. This study further demonstrates how susceptible these systems are to inefficiency by finding that negative shocks to energy efficiency are more detrimental than positive ones. Green investments, when coupled with energy efficiency and trade liberalisation, can reduce competitiveness in the short term while leading to sustainability in the long run. This study takes a novel approach by presenting green finance as a critical link between foreign direct investment (FDI) and sustainable development. It demonstrates how green finance can transform resource-based economies' industrial growth driven by FDI into development that is both more energy-efficient and environmentally friendly.